Frequency of Hypogonadism and Erectile Dysfunction in Type-II Diabetic Patients - Mushtaq, Samsam (Cureus, 2018)
Introduction: The persistent state of hyperglycemia in diabetes mellitus predisposes diabetic patients to suffer from neuropathy, vasculopathy, and endocrinological changes. Hypogonadism and erectile dysfunction are commonly observed in diabetic patients secondary to androgen deficiency. In the developing world, patients usually under-report their sexual dysfunction. We conducted this study to determine the frequency of hypogonadism and erectile dysfunction and the associated risk factors in type-II diabetic male patients presenting in the outpatient department of a tertiary care hospital in Pakistan. Methods: This was an observational, cross-sectional hospital-based study conducted at Jinnah Allama Iqbal Institute of Diabetes and Endocrinology (JAIDE), Allama Iqbal Medical College/Jinnah Hospital, Lahore, Pakistan from April 2017 to October 2017. One hundred and sixty type-II diabetic patients meeting the inclusion criteria were enrolled in the study after informed consent. All patients were given the International Index of Erectile Function (IIEF) questionnaire to determine the severity of erectile dysfunction. Patients were tested for serum total testosterone levels and hypogonadism labeled if the serum testosterone level came out to be less than 8 nmol/L with or without symptoms of hypogonadism or with a testosterone level of 8-12 nmol/L and symptoms of hypogonadism. Results: The mean age of the patients was 51.2 ± 11.5 years (range: 31 – 60 years). The mean duration of type-II diabetes mellitus was 8.3 ± 5.1 years. The frequency of erectile dysfunction was found to be 62.5%. Mild erectile dysfunction was seen in 19 patients (11.9%), mild to moderate in 15 patients (9.4%), moderate in 42 patients (26.2%), and severe in 24 patients (15.0%) with an IIEF score of 17-21, 12-16, 8-11, and 1-7, respectively. More severe erectile dysfunction was seen in patients with a prolonged history of diabetes (p-value <0.0001). The mean testosterone level was 18.1 + 8.4 (range: 0.31-38.1) nmol/L. Based on our criteria, hypogonadism was seen in 61 patients (38.1%) with 29 (18.1%) and 32 (20.0%) suffering from severe and mild forms of hypogonadism, respectively. Forty percent of the patients with erectile dysfunction suffered from some form of hypogonadism with subnormal testosterone levels. The difference in the testosterone level of patients with and without erectile dysfunction was statistically significant (p-value: 0.0001). Conclusion: Patients suffering from type-II diabetes mellitus had a significantly greater frequency of erectile dysfunction and hypogonadism. Diabetic patients should be counseled and treated for these issues to improve their quality of life, especially in under-developed countries where sexual health problems are seldom reported.